Microplastics Alter Growth and Reproduction Strategy of Scirpus mariqueter by Modifying Soil Nutrient Availability - Pengcheng Jiang; Jingwen Gao; Junzhen Li; Ming Wu; Xuexin Shao; Niu Li (Diversity, 2025)
Microplastic pollution threatens coastal wetland ecosystems, yet its impacts on the dominant plant species and soil properties remain poorly understood. We investigated the effects of four microplastic types (PP, PE, PS, PET) at three concentrations (0.1%, 0.5%, 1% w/w) on Scirpus mariqueter, a keystone species in the coastal wetlands of China, and the associated soil physicochemical properties. In a controlled pot experiment, microplastics significantly altered the plant biomass, vegetative traits, and reproductive strategies, with type-specific and concentration-dependent responses. PET and PE strongly suppressed the belowground and total biomass (p < 0.05), with reductions in the belowground biomass of 42.87% and 44.13%, respectively, at a 0.1% concentration. PP promoted seed production, particularly increasing the seed number by 25.23% at a 0.1% concentration (p < 0.05). The soil NH4+-N, moisture, and EC were key mediators, with NH4+-N declines linked to biomass reductions via nitrogen limitation. The Spearman correlations confirmed strong associations between the plant traits and soil properties, particularly nitrogen forms. These findings reveal that microplastics disrupt wetland plant performance and soil environments, potentially impairing carbon sequestration and ecosystem stability. Our study underscores the urgent need for microplastic risk assessments in coastal wetlands and highlights soil–microbe–plant interactions as critical mechanisms for future investigation.